Funding identity: Hungary's efforts to preserve its minority in Slovakia - Grega Ferenc (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2025)
This paper presents causal evidence on how financial aid for Hungarian minorities in Slovakia leads to their non-assimilation. Using a staggered panel event study design, I show that the introduction of financial aid by the Hungarian government led to a statistically significant 2.35 percentage points increase in the yearly rate of change in the share of Hungarians in the first post-treatment period relative to the pre-treatment period. In subsequent years, the effect diminishes to around one percentage point relative to the baseline. When excluding all infrastructure investments from the analysis, the effect in the first post-treatment period is significant and positive. However, it completely levels off in the following periods. The results could suggest that while Hungarian investments in culture are important, they have to be complemented by adequate investments in infrastructure to ensure that more people identify as Hungarians in Slovakia. The results could have implications not only for Hungarians living in Slovakia and other countries but also for the future of European minority protection programs, as laid down in the relevant international legal documents, such as the International Covenant on Civil and Political Rights or the Copenhagen criteria of the European Union. This research should pave the way for future analyses on the prevention of assimilation of autochthonous ethnic minorities worldwide.
Keywords: F59; F68; J15; 330; Minorities; Assimilation; Prevention; Hungary; Financial Aid